2023
DOI: 10.3390/foods12061275
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Physicochemical, Functional, Microbiological and Sensory Properties of Yoghurts Using Plant Additives

Abstract: Nowadays, consumers pay particular attention to the quality of the products they buy. They also expect a high level of innovation. Hence, the offer from the dairy sector is increasingly focusing on the use of various additives with proven health benefits. Many scientific teams from various regions of the world are engaged in research, and their aim is to identify plant additives that have beneficial effects on the human body. The aim of this article was to summarize the latest literature pertaining to the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…With increasing the concentration of green pepper extract in yogurt, the amount of syneresis increased. In fact, with the increase in the activity of lactic acid bacteria followed by a decrease in pH, the strength of the yogurt gel network decreases and as a result, syneresis increases in yogurt ( Wajs, Brodziak, & Król, 2023 ). The decrease in pH changes the natural form of the protein and due to the denaturation of the protein, the water bound to it is released, and Syneresis increases ( Lee & Lucey, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…With increasing the concentration of green pepper extract in yogurt, the amount of syneresis increased. In fact, with the increase in the activity of lactic acid bacteria followed by a decrease in pH, the strength of the yogurt gel network decreases and as a result, syneresis increases in yogurt ( Wajs, Brodziak, & Król, 2023 ). The decrease in pH changes the natural form of the protein and due to the denaturation of the protein, the water bound to it is released, and Syneresis increases ( Lee & Lucey, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the sensory evaluation of the product tends to deteriorate with the increased presence of additives. It is therefore important to conduct test production to optimize the amount of the additive when designing a new product [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decades of research suggest that yoghurt consumption is associated with numerous nutritional benefits. In a recent report, Wajs et al ( 6 ) concluded that “superfood” yoghurt has emerged as one of the food products being recommended increasingly for both preventive and ameliorative dietary therapy against civilization diseases, including diabetes mellitus, neurodegenerative diseases and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known for its richness in health-promoting constituents. Bioactive peptides and bacteriocins, capable of reducing lactose content in dairy products, are also produced during the fermentation process of yoghurt and this is beneficial to consumers with lactose intolerance ( 6 , 8 ). The live bacteria, also known as probiotics, in yoghurt aid in reducing digestive problems, such as constipation, bloating, and diarrhoea ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation